A Chronological List of References on Switched Capacitor Circuits. (1982) - Vandewalle, J.
Abstract : A chronological list of 440 references on switched capacitor circuits is compiled. Such circuits have cut the cost of filters and signal processing devices for telecommunications, speech and consumer products because they can be easily integrated on a chip. The bibliography shows the explosion of interest since 1977 by IC designers, CAD developers and circuit and filter theorists and practitioners alike. Very specialized publications as well as elementary papers and books have been included.